STUDI KOORDINASI SISTEM PENGAMAN PADA TRANSFORMATOR DAYA PT. PLN (PERSERO) P3B SUB REGION BALI DI GARDU INDUK PADANG SAMBIAN - I Putu Chandra Adinata; AA Gede Maharta Pamayun; Antonius Ibi Weking (Program Studi Teknik Elektro UNUD, 2020)
The transformer is the main equipment that is very important at the substation.However, sometimes there can be damage to the transformer used. Damage to the transformerwill be able to disrupt the distribution of electricity, so it must get the right security, determiningthe right relay setting is an attempt to protect equipment, system security and consumer needsfrom possible disruption in the distribution system. In some roles, efforts to protect the powertransformer if there is a short circuit between phase and phase to the ground, then this study willstudy the coordination of the security system of power transformers in Padang Sambian mainsubstation. The results of the calculation of overcurrent relay (OCR) on the 150KV transformerthat has been done is obtained the results of the CT primary side current setting of 254.1 A andfor the secondary side of 3.178 A. For the actual working time of the relay is 0.91 seconds, if thecurrent exceeds value of this setting there will be a trip. The results of the calculation ofovercurrent relay (OCR) on the 20KV transformer that has been done is obtained the results ofthe CT primary side current setting of 1905 A and for the secondary side is obtained for 4.76 A.For the actual working time relay result is 3.69 seconds, if the current exceeds the value of thissetting there will be a trip.